2017
DOI: 10.2147/cia.s137570
|View full text |Cite
|
Sign up to set email alerts
|

Mortality after major amputation in elderly patients with critical limb ischemia

Abstract: BackgroundOwing to the aging population, the number of elderly patients with critical limb ischemia (CLI) has increased. The consequence of amputation is immense. However, at the moment, information about the mortality after amputation in the elderly vascular patients is unknown. For this reason, this study evaluated mortality rates and patient-related factors associated with mortality after a major amputation in elderly patients with CLI.MethodsFrom 2006 to 2013, we included patients aged >70 years who were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 15 publications
2
62
0
2
Order By: Relevance
“…9 Our results endorse these findings in patients with CLI. Because of high amputation rates (35%e67%) 3,8,30 in CLI, a valid QoL outcome and HS is important in vascular amputees. In our study, vascular amputees (with a one-year mortality of 35%) showed statistically significant improvement in the physical QoL domain at one-year follow-up (survey response 67%, n ¼ 20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Our results endorse these findings in patients with CLI. Because of high amputation rates (35%e67%) 3,8,30 in CLI, a valid QoL outcome and HS is important in vascular amputees. In our study, vascular amputees (with a one-year mortality of 35%) showed statistically significant improvement in the physical QoL domain at one-year follow-up (survey response 67%, n ¼ 20).…”
Section: Discussionmentioning
confidence: 99%
“…1 CLI, the end stage of peripheral arterial disease, is also the most common cause of major limb amputation in elderly patients. 2,3 Because major limb amputation is usually associated with poor physical function, high mortality, and assumed high revalidation costs, it is an outcome that health care providers fear. 3e6 However, in the elderly CLI patients, revascularization is not always possible and major limb amputation is often necessary, due to infection or severe pain in selected patients.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, despite the available treatments, it is difficult to achieve wound healing, and unhealed wounds persist in many patients. The prognosis and risk factors for death after EVT and those after major amputation of a lower limb have been investigated in advanced treatment centres. At these sites, satisfactory revascularisation using repeat EVT or bypass surgery cannot be performed in some cases with poor general conditions, and amputation of the lower limb is not always applicable, although it may be necessary in certain cases.…”
Section: Discussionmentioning
confidence: 99%
“…53 Studies comparing primary amputation versus amputation following revascularization among the elderly are mixed, with some finding higher rates of mortality following failed bypass. 54,55 The decision regarding revascularization versus amputation is a difficult and personal choice. This should involve a thoughtful discussion with the patient regarding appropriate expectations and outcomes.…”
Section: Patient Selection For Major Amputation In Cltimentioning
confidence: 99%
“…Long-term outcomes following major amputation remain poor, with relatively high rates of perioperative and longterm mortality. 54,68 Mustapha et al demonstrated that patients with CLTI treated with primary amputation had significantly lower rates of survival and a higher risk of subsequent amputation over 4 years compared with revascularization. 69 Even after propensity matching, those who underwent primary major amputation had a mean survival of 1.3 years compared with 2.7 and 2.9 years with endovascular and open revascularization, respectively.…”
Section: The Impact and Outcomes Of Major Amputationmentioning
confidence: 99%